2021
DOI: 10.1590/1806-9061-2020-1334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Storage Period, Marketing Channels and Season on Internal and External Quality of Commercial Table Eggs Marketed in Riyadh City (Saudi Arabia)

Abstract: Very sparse information is available regarding quality of commercial Table eggs marketed in Riyadh city. The objective of the current study was to evaluate egg quality by determining the internal and external traits of commercial Table eggs marketed in different marketing channels during the summer and winter. Commercial eggs (n = 1440) were bought from four different supermarkets and groceries during the winter and summer season 2018-2019. A total of 30 eggs were collected monthly from each marketing channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The findings also indicated that longer storage periods resulted in a faster rate of change in trait scores. The study showed that ten, twenty and thirty days of storage duration resulted in a significant (p0.05) decrease in Haugh unit values, yolk weight ratio, specific density, shell thickness and shell weight per unit of surface area, as well as an increase in yolk color grade, yolk albumin ratio and air cell depth; however, shape index and shell density were unaffected by storage length (Alsobayel and Albadry, 2011;Alshaikhi et al, 2021). Similar storage length effects were reported by several researchers for Haugh unit values and the yolk index.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings also indicated that longer storage periods resulted in a faster rate of change in trait scores. The study showed that ten, twenty and thirty days of storage duration resulted in a significant (p0.05) decrease in Haugh unit values, yolk weight ratio, specific density, shell thickness and shell weight per unit of surface area, as well as an increase in yolk color grade, yolk albumin ratio and air cell depth; however, shape index and shell density were unaffected by storage length (Alsobayel and Albadry, 2011;Alshaikhi et al, 2021). Similar storage length effects were reported by several researchers for Haugh unit values and the yolk index.…”
Section: Resultsmentioning
confidence: 99%
“…The products of laying hens play an important role in meeting human nutritional needs that help them stay healthy (Alshaikhi et al, 2021). Eggs are a vital food source for humans because they contain animal protein, fats, mineral salts, essential amino acids, saturated fats, yeasts and enzymes that are only found in a few foods (Sahar and Rahman, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the results of the evaluation of the sensory characteristics of the eggs carried out by Attia et al [ 34 ] showed that eggs stored at 5 °C were better than eggs stored at 23 °C. According to Alshaikhi et al [ 33 ], poorer results in the evaluation of the sensory characteristics of eggs during storage at higher temperatures are due to an increase in evaporation and migration of water from the white to the yolk, leading to a reduction in the concentration of nutrients in the yolk. In a study by Aguinaga Bósquez et al [ 74 ], based on human sensory evaluation, there was no effect of storage time on the characteristics of cooked eggs; however, the use of advanced analytical methods, such as e-tongue and e-nose, showed an effect of storage time (0, 30, and 60 days) on the sensory characteristics of eggs.…”
Section: Resultsmentioning
confidence: 99%
“…Sensory evaluation most often takes into account color, taste, and odor [ 31 ]. Storage time and conditions can affect the sensory quality of eggs [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, excess dietary fluoride affected the formation of eggshell, reducing eggshell strength and thickness (Miao et al, 2017). Feeding conditions are also key factors for egg quality (Alshaikhi et al, 2021). Sudden increases in temperature and humidity can cause lowered immunity in laying hens (Soliman & Safwat, 2020).…”
Section: Introductionmentioning
confidence: 99%